Long Noncoding RNA POU3F3 and α-Synuclein in Plasma L1CAM Exosomes Combined with β-Glucocerebrosidase Activity: Potential Predictors of Parkinson's Disease - Zou, Jing; Guo, Yue; Wei, Lei; Yu, Fang; Yu, Bo; Xu, Anding (Neurotherapeutics, 2020)
Long noncoding RNAs (lncRNAs) are implicated in the autophagic-lysosomal pathway (ALP) and are closely linked to Parkinson's disease (PD) pathology. β-Glucocerebrosidase (GCase) has also been reported to be correlated with α-synuclein (α-syn) proteostasis. However, lncRNAs and α-syn in neural-derived L1CAM exosomes and GCase activity in the plasma of PD patients have not been studied. This study used an ultrasensitive methodology, fluorescence nanoparticle tracking analysis (NTA), to measure plasma L1CAM exosomes and Quanterix Simoa to measure α-syn concentrations in L1CAM exosomes. Eighty-five healthy controls and 93 PD patients were enrolled, and several scales were used to rate the severity of PD. Receiver operating characteristic (ROC) curves were applied to map the diagnostic accuracy of categorizing PD patients and healthy subjects. We found increased Linc-POU3F3 and α-syn concentrations in L1CAM exosomes and decreased GCase activity in PD patients compared with controls. The three biomarkers displayed obvious differences among PD patients based on gender, H-Y stage, and UPDRS-III distribution. Interestingly, Linc-POU3F3 was significantly positively correlated with α-syn in L1CAM exosomes and inversely correlated with GCase activity in PD patients. Significant correlations were observed among L1CAM exosomal Linc-POU3F3 levels, GCase activity, and PD severity, including motor/cognitive dysfunction. Additionally, the combination of Linc-POU3F3 and α-syn in L1CAM exosomes and GCase activity could discriminate PD patients from controls. These results suggest that L1CAM exosomal Linc-POU3F3, L1CAM exosomal α-syn, and GCase activity may shed light on the mechanism underlying the autophagic-lysosomal system in the pathogenesis of PD and could be used to assess the severity of PD.